2017
DOI: 10.3389/fnhum.2017.00052
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age, from Young to Middle Adulthood, and Gender on Resting State Functional Connectivity of the Dopaminergic Midbrain

Abstract: Dysfunction of the dopaminergic ventral tegmental area (VTA) and substantia nigra pars compacta (SNc) is implicated in psychiatric disorders including attention-deficit/ hyperactivity disorder (ADHD), addiction, schizophrenia and movement disorders such as Parkinson’s disease (PD). Although the prevalence of these disorders varies by age and sex, the underlying neural mechanism is not well understood. The objective of this study was to delineate the distinct resting state functional connectivity (rsFC) of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 135 publications
(204 reference statements)
2
15
0
Order By: Relevance
“…Dennis and Melzack demonstrated that dopaminergic agents improve symptoms of pain and promote analgesia [98]. Studies have also shown that the VTA sends projections to the nucleus accumbens (NCs), limbic system (e.g., hippocampus and amygdala), and prefrontal cortex (e.g., mPFC, ACC, and OFC), forming the mesocorticolimbic system [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dennis and Melzack demonstrated that dopaminergic agents improve symptoms of pain and promote analgesia [98]. Studies have also shown that the VTA sends projections to the nucleus accumbens (NCs), limbic system (e.g., hippocampus and amygdala), and prefrontal cortex (e.g., mPFC, ACC, and OFC), forming the mesocorticolimbic system [27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that chronic pain is a hypodopaminergic state [24][25][26]. The ventral tegmental area (VTA), a key structure in the midbrain, sends dopaminergic neural projections to the ventral striatum (i.e., nucleus accumbens), limbic system (e.g., hippocampus and amygdala), and prefrontal cortex (e.g., mPFC, ACC, and OFC), forming the mesocorticolimbic system [27][28][29][30][31]. In a recent study, we found that chronic low back pain was associated with VTA functional connectivity alterations [32], and preclinical studies have suggested that targeting reward/motivation circuits may promote recovery from chronic pain [23].…”
Section: Introductionmentioning
confidence: 99%
“…Brain imaging data were preprocessed using Statistical Parametric Mapping (SPM 8, Wellcome Department of Imaging Neuroscience, University College London, United Kingdom) following previous work ( Kann et al, 2016 ; Li et al, 2017 ; Peterson et al, 2017 ; Zhang S. et al, 2017 ; Hu et al, 2018 ). Images from the first five TRs at the beginning of each trial were discarded to enable the signal to achieve steady-state equilibrium between RF pulsing and relaxation.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic, biological, and chemical sex‐related differences are known to influence specific physiological variables, which can, in turn, affect fMRI signal . Indeed, previous RS and task‐related fMRI studies have shown both topological and regional sex‐related differences in healthy subjects, some specific for dopamine‐related functions . Nevertheless, to date there is no fMRI study investigating the neural correlates of sex difference in PD patients.…”
mentioning
confidence: 99%